A religião como espaço de integração da vida comunitária na Comunidade Cristã Paz e Vida em tempos de Covid-19 - Coelho, André Magalhães (2022)
This doctoral thesis presents a study on religion as a space for the integration of community life in the Christian Peace and Life Community, in times of pandemic. Located on the outskirts of the East Zone of São Paulo, these evangelical churches produce structures to direct their faithful, through emotional support in the face of crises caused by social isolation. The objective is to understand the presence of the religious person in the symbolic spaces of the church in times of Covid-19. In this way, it is worth studying to understand the religious discourse of this institution, as well as the resignification of religious practices and the use of technologies so that religious services can persist without face-to-face meetings at a time when the pandemic was with a high rate of contagion in Brazil. In my approach to the church, through visits and approach to the church that I made the religious institution in 2020, it is soon possible to observe how the religious field is complex and the opinions in the churchreligious institution are not homogeneous. eAlthough it believes that the virus is a form of theodicy, Paz e Vida defends social distancing and criticizes actions that are against science. The empirical material collected for this research is formed by: 02 (two) pastors called Pastor A and Pastor B, 03 (three) church members who will be called Members A, B, C and 03 (three), Workers,, who will be presented as Workers A, B, C. The research was developed based on field observation and interactions produced by the faithful and the religious leader through Facebook, YouTube, the church website and the WhatsApp application, in order to verify and understand their responses to the Covid-19 pandemic. For this, bibliographic readings, interviews and field observations were used, as well as the use of questionnaires to be answered by the members